Metal-organic frameworks: Drug delivery applications and future prospects - Prachi Mhettar; Niraj Kale; Jidnyasa Pantwalawalkar; Sopan Nangare; Namdeo Jadhav (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: Metal-organic frameworks (MOFs) have gained incredible consideration in the biomedical field due to their flexible structural configuration, tunable pore size and tailorable surface modification. These inherent characteristics of MOFs portray numerous merits as potential drug carriers, depicting improved drug loading, site-specific drug delivery, biocompatibility, biodegradability, etc. Review approach: The current review article sheds light on the synthesis and use of MOFs in drug delivery applications. In the beginning, a brief overview of the key components and efficient fabrication techniques for MOF synthesis, along with its characterization methods, have been presented. The MOFs-based formulations have been critically discussed. The application of the design of experiments (DoE) approach to optimize MOFs has been elucidated. The MOFs-based formulations, especially the application of stimuli-responsive MOFs for site-specific drug delivery, have been deciphered. Along with drug release kinetic models, several administration methods for MOFs have also been enunciated. Subsequently, MOFs as future potential drug carriers have been elaborated. Key results and conclusion: Recently, MOFs have emerged as versatile drug delivery carriers possessing customization potential and meeting the needs of spatio-temporal drug delivery. Researchers have devised several environment-friendly approaches for MOF construction and surface modification. Owing to stimuli-responsive potential, MOFs have demonstrated their prominent therapeutic efficacy via several routes of administration. The numerous benefits of MOFs would certainly open up a new vista for its novel drug delivery applications.